Developing an environmental equity index for urban heat wave event - Xiaohui Ma; Li Zhang; Xiaochun Yang; Yue Fan; Fukuda Hiroatsu; Jiahao Zhang; Luyao Li (Environmental and Sustainability Indicators)
Societal “imbalance” and “injustice” are key concerns during heatwaves that are considered a typical climate change phenomenon. However, our understanding of precise ways to measure and respond to environmental justice needs remains limited. In this study, we develop an equity index to examine environmental justice problems with respect to social resource provisions during heatwave responses. A multi-source data integration approach and a synthetic population algorithm are used to construct a method to calculate environmental equity indices with 100∗100 m spatial resolution. The resultant integrated equity index map offers a comprehensive view of the urgent need for social resource provision during heatwave responses. Our findings reveal that, despite a higher demand for heatwave-related resources in central urban areas, some suburban regions, particularly emerging cross-boundary functional zones, exhibited lower levels of equity due to inadequate social resource supplies. Additionally, we explored the correlation between social media data based heatwave perception maps and environmental equity levels, confirming the potential of using the heatwave perception to validate the equity index. This study not only mapped out priority areas but also set the stage for targeted interventions to enhance resilience and justice in urban planning.